Is second-line systemic chemotherapy beneficial in patients with non-small cell lung cancer (NSCLC)? A multicenter data evaluation by the Anatolian Society of Medical Oncology - DANE, FAYSAL (SAGE PUBLICATIONS LTD, 2015)
Patients with advanced non-small cell lung cancer (NSCLC) generally require second-line treatment although their prognosis is poor. In this multicenter study, we aimed to detect the characteristics related to patients and disease that can predict the response to second-line treatments in advanced NSCLC. Data of 904 patients who have progressed after receiving first-line platinum-based chemotherapy in 11 centers with the diagnosis of stage IIIB and IV NSCLC and who were evaluated for second-line treatment were retrospectively analyzed. The role of different factors in determining the benefit of second-line treatment was analyzed. Median age of patients was 57 years (range 19-86). Docetaxel was the most commonly used (20.9 %, n = 189) single agent, while gemcitabine-platinum was the most commonly used (6.7 %, n = 61) combination chemotherapy regimen in second-line setting. According to survival analysis, median progression-free survival after first-line treatment (PFS2) was 3.5 months (standard error (SE) 0.2; 95 % confidence interval (CI), 3.2-3.9), median overall survival (OS) was 6.7 months (SE 0.3; 95 % CI, 6.0-7.3). In multivariate analysis, independent factors affecting PFS2 were found to be hemoglobin (Hb) level over 12 g/dl and treatment-free interval (TFI) longer than 3 months (p = 0.006 and 0.003, respectively). Similarly, in OS analysis, Hb level over 12 g/dl and time elapsed after the first-line treatment that is longer than 3 months were found to be independent prognostic factors (p = 0.0001 and 0.045, respectively). In light of these findings, determining and using the parameters for which the treatment will be beneficial prior to second-line treatment can increase success rate.
Keywords: Hemoglobin level; Non-small cell lung cancer; Second-line treatment; Prognostic factors; Survival; PHASE-III TRIAL; PLATINUM-BASED CHEMOTHERAPY; SUPPORTIVE CARE; DOCETAXEL; METASTASIS; ERLOTINIB; SURVIVAL